Ethical Principles in Medicine: A Deeper Reflection on Autonomy, Beneficence, Nonmaleficence, and Justice in Current Medical Practice - Akter, Shaima; Salam, Md Mushtahid; Yousuf, Rabeya; Al Mahmood, Abu Kholdun; Salam, Abdus (International Journal of Human and Health Sciences (IJHHS), 2025)
Abstract not available International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 139-142